The Art Newspaper (vanaf 1994 ook Franse editie : Le Journal des Arts; The Art Newspaper France (2018); The Art Newspaper Russia (2012); The Art Newspaper Israel (2019); The Art Newspaper China (2013). (Londen : The Art Newspaper, 1983)
The Art Newspaper is a monthly print publication, with daily updates online, founded in 1990 and based in London and New York City. It covers news of the visual arts as they are affected by international politics and economics, developments in law, tax, the art market, the environment and official cultural policy.(Wikipedia)
Https://www.theartnewspaper.com
11 times a year (not in August)
Engels
Frans
Tijdschriften